O laboratório proinfo: uso e apropriação das tecnologias educacionais por parte dos professores - Apolinário, Maria Joseneide (2014)
The present study investigated the use and ownership that teachers and teachers make educational technology in school laboratories implemented by the Ministry of Education (MEC) through the National Program of Educational Technology (ProInfo). ProInfo was created initially by the MEC in 1997 and in 2007 became the National Program of Educational Technology, with the main objective to promote the educational use of information and communication at public basic education technologies. The questions were: after so long there are monitoring and evaluating the use of technology in schools Laboratories ProInfo the country? Held in basic education schools I and II, the municipal schools in a large city of São Paulo ¹, the survey asked: what educational technologies reached the schools in the network; know how teachers are appropriating these educational practices; identifying and motivating activities for students and teachers that enabled the production of new knowledge. The methodology consisted of a case study, and information was obtained from open and closed questionnaire on school visits, analysis of documents from the Secretary of Education, observation of activities developed by teachers, portfolios, and reports of teachers and the management team. For the intervention was an accomplished Culture Circle with teachers at a school of municipal schools, with the aim of analyzing their practices ( or not) in the computer labs ProInfo, and share strategies for teaching and learning, integrating technological resources ProInfo. The survey allowed us to know this particular situation and understand the need for the use of technological devices and instruments to mobilize certain knowledge and recreate the teaching practice that allows the teacher to intervene and is critically appropriate educational technologies in laboratories ProInfo. In this sense, the experience allowed the experience of new learning, in which was reflected in many ways, a certain educational project produced from the inquiry into the laboratories, exchange of experiences, the sharing of knowledge, readings and reflections, generating new challenges.